Optimization of The Role of Protocol and Communication of The Leadership of The Regional Secretary Office Sikka Regency in Public Information Services - Galgani Yolanda; Lodowik Nikodemus Kedoh; Viktor Ariestyan Sedu (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This study aims to examine the optimization of the role of the Protocol and Communication of the Leadership (Prokompim) of the Sikka Regency Secretariat in providing public information services through the Sikka Buletin Facebook account. The focus of the study is to evaluate the effectiveness of social media content management and communication strategies to increase public involvement. A qualitative approach is used to describe content management based on observations, interviews, and documentation studies. Data were collected through interviews with the admin of the Sikka Buletin Facebook account and followers as well as analysis of published content. The data analysis technique adopted the Flow Analysis Models of Miles and Huberman, which include data reduction, data presentation, and verification to produce in-depth understanding. The results of the study indicate that although Prokompim has attempted to manage content using the 5W1H elements with a formal but relaxed communication style, there are still challenges in increasing audience engagement. The main findings include low public interaction with posted content and less than optimal time and collaboration in content management. This study recommends a more planned time management strategy, collaboration with related agencies to enrich content, and a focus on audience engagement to strengthen the relationship between the government and the community through social media.